Thermal Decomposition Kinetics of High Impact Polystyrene/ Organo Fe-montmorillonite Nanocomposites - 刘宏 孔庆红 程宇和 曹功源 (Chinese journal of chemistry, 2012)
In this article, high impact polystyrene/organo Fe-montmorillonite （HIPS/Fe-OMT） nanocomposites were prepared by melting intercalation. The thermal stability of HIPS/Fe-OMT nanocomposites increased significantly compared to that of HIPS examined in thermal degradation conditions. Kinetic evaluations were performed by Kissinger, Flynn-Wall-Ozawa, Friedman methods and multivariate nonlinear regression. Apparent kinetic parameters for the overall degradation were determined. The resuRs showed that the activation energy of HIPS/Fe-OMT nanocomposites was higher than that of HIPS. A very good agreement between experimental and simulated curves was observed in dynamic conditions. Their decomposition reaction model was a single-step process of an nth-order reaction